Epistemic modality in translated and non-translated English court judgments of Hong Kong: A corpus-based study - Su, Yanfang; Liu, Kanglong; K. F. Cheung, Andrew (The Journal of Specialised Translation, 2023)
Court judgments serve as important precedents for future judicial decision-making in common law systems. The legal meanings of judgments are conveyed by specific linguistic devices, among which epistemic modality plays an important role in indicating the probability of propositions to construct convincing arguments and recognise potential differing opinions (Abbuhl 2006). This study adopts a corpus-based approach to compare different categories of epistemic modality in translated and non-translated English court judgments in Hong Kong. Based on the framework put forward in Halliday and Matthiessen (2004), epistemic modality is categorised by orientation, value, and linguistic realisation. The findings reveal that the non-translated court judgments are characterised by a higher proportion of epistemic modality. In terms of orientation, the two corpora also exhibit some different distribution patterns. As for value, the overwhelming proportion is represented by median-value epistemic modality markers, whereas high-level modality markers are least represented in both corpora. Some variations related to the linguistic realisation of epistemic modality were also observed between the two corpora, which could mainly be attributed to the influence of the Chinese source texts, the translation process and different judicial thinking.